2009
DOI: 10.1073/pnas.0812082106
|View full text |Cite
|
Sign up to set email alerts
|

Candicidin-producing Streptomyces support leaf-cutting ants to protect their fungus garden against the pathogenic fungus Escovopsis

Abstract: Leaf-cutting ants such as Acromyrmex octospinosus live in obligate symbiosis with fungi of the genus Leucoagaricus, which they grow with harvested leaf material. The symbiotic fungi, in turn, serve as a major food source for the ants. This mutualistic relation is disturbed by the specialized pathogenic fungus Escovopsis sp., which can overcome Leucoagaricus sp. and thus destroy the ant colony. Microbial symbionts of leaf-cutting ants have been suggested to protect the fungus garden against Escovopsis by produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
231
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(253 citation statements)
references
References 35 publications
15
231
0
7
Order By: Relevance
“…Another study, employing the culture-independent analysis of membrane-lipid markers, has supported the hypothesis that a distinct community of predominantly Gram-negative bacteria resides in fungus gardens , and the presence of symbiotic nitrogen-fixing bacteria in the genera Pantoea and Klebsiella has also been shown (Pinto-Tomas et al, 2009). Together with culture-dependent investigations recovering microbial groups with a broad array of metabolic activities (Bacci et al, 1995;Santos et al, 2004), these experiments have led to the suggestion that fungus gardens represent specialized fungusbacteria consortia selected for by the ants, and that the bacteria have essential roles, including plant biomass degradation, nutrient biosynthesis, and competitive or antibiotic-mediated exclusion of pathogens (Mueller et al, 2005;Haeder et al, 2009;Pinto-Tomas et al, 2009;Suen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another study, employing the culture-independent analysis of membrane-lipid markers, has supported the hypothesis that a distinct community of predominantly Gram-negative bacteria resides in fungus gardens , and the presence of symbiotic nitrogen-fixing bacteria in the genera Pantoea and Klebsiella has also been shown (Pinto-Tomas et al, 2009). Together with culture-dependent investigations recovering microbial groups with a broad array of metabolic activities (Bacci et al, 1995;Santos et al, 2004), these experiments have led to the suggestion that fungus gardens represent specialized fungusbacteria consortia selected for by the ants, and that the bacteria have essential roles, including plant biomass degradation, nutrient biosynthesis, and competitive or antibiotic-mediated exclusion of pathogens (Mueller et al, 2005;Haeder et al, 2009;Pinto-Tomas et al, 2009;Suen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…From A. octospinosus, Barke et al (13) detected, besides the presence of the previously characterized candicidin polyene macrolide-producing Streptomyces (11), a Pseudonocardia symbiont that produces a nystatin-like polyene macrolide. These recent findings indicated that there are likely to be a number of diverse antifungal compounds yet to be identified from microbial symbionts of leaf-cutting/fungus-growing ants (11)(12)(13).…”
mentioning
confidence: 99%
“…Although isolated microbial symbionts were active against Escovopsis in the agar diffusion assay (10), until recently, not a single compound from the ants' microbial symbionts had been characterized. Using bioassay-guided isolation, Haeder et al (11) identified the antifungal candicidin macrolides that are produced by a large number of Streptomyces symbionts isolated from three different leaf-cutting ant species (A. octospinosus, A. echinatior, and A. volcanus). For the fungus-growing ant Apterostigma dentigerum, Oh et al (12) reported the cyclodepsipeptide dentigerumycin from a Pseudonocardia symbiont with activity against E. weberi.…”
mentioning
confidence: 99%
“…The most prominent microbes thought to be involved in disease-suppression in attine gardens are actinomycete bacteria in the genus Pseudonocardia, which accumulate on the ants' bodies mixed into integumental accretions of likely glandular origin (12)(13)(14). Many of the ant-associated Pseudonocardia species show antibiotic activity in vitro against Escovopsis (13)(14)(15). A diversity of actinomycete bacteria including Pseudonocardia also occur in the ant gardens, in the soil surrounding attine nests, and possibly in the substrate used by the ants for fungiculture (16,17).…”
mentioning
confidence: 99%